How can anticipatory action programming support women? Application of the reach-benefit-empower-transform framework in Nepal and Nigeria - Gonzales, Teresa; Kosec, Katrina; Kyle, Jordan; Madero, Ana; Mittrick, Caitlin; Myers, Emily; Quisumbing, Agnes R.; Rapadas, Amica (International Food Policy Research Institute, 2024)
As floods increase in frequency and intensity due to climate change, anticipatory action (AA) programs offer a promising approach to mitigate their impacts. However, there is limited research about how AA programming can address the specific needs of women, who often face heightened vulnerabilities during disasters. This paper applies the Reach, Benefit, Empower, Transform (RBET) framework to examine gender dynamics in AA programming through case studies in Nepal and Nigeria—two flood-prone countries where AA initiatives have been piloted. Using data from key informant interviews and focus group discussions with stakeholders, including government agencies, NGOs, local advocacy groups, and direct beneficiaries of flood programs, we assess barriers and enabling conditions for AA to reach, benefit, and empower women and broader opportunities for transformation of gender norms and social inequalities. Our findings reveal key implementation challenges, including limited funding, weak integration with broader disaster risk reduction efforts, and inadequate early warning systems. However, we also identify practical strategies for improving AA’s gender responsiveness, such as relying on individual rather than household-level data, providing accessible early warning information, offering aid modalities that meet women’s specific needs (such as dignity kits), ensuring women’s participation in community decision-making, and facilitating ongoing inclusive household and community dialogues in flood-prone communities rather than only responding to specific flood warnings. The paper concludes with recommendations for scaling up gender-inclusive AA programming to enhance resilience and reduce the disproportionate impacts of flooding on women.